The Effect of Training, Supervision and Occupational Safety and Health (K3) Culture on Employee Performance: Pengaruh Pelatihan, Pengawasan Dan Budaya Keselamatan Dan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan - Setiawan, Fredy; Astutik, Mudji (Indonesian Journal of Law and Economics Review, 2022)
The purpose of this study was to determine the effect of training, supervision, and occupational safety and health (K3) culture on employee performance either partially or simultaneously. And to find out the most significant influence between the influence of Training, Supervision, and Occupational Safety and Health (K3) Culture on Employee Performance at PT. Maspion Electronic Sidoarjo The data in this study used tabulated data from respondents from the questionnaire results. The sample used in this study were 83 employees at PT. Maspion Electronic Sidoarjo. This primary data was obtained from a questionnaire whose measurement was using a Likert scale which was tested for validity and reliability. The analysis used is multiple linear regression analysis, coefficient of determination (R2), partial correlation coefficient, t test, F test and classical assumption test using SPSS program. This research results that training has an effect on performance, supervision has an effect on performance, and occupational safety and health (K3) culture has an effect on performance. and training, supervision, and occupational safety and health (K3) culture affect performance. Variables of training, supervision, and occupational safety and health (K3) culture have an effect on performance and have a strong and direct relationship to employee performance.